Stolen girl [videorecording (DVD)] - Beckinsale, Kate; Eastwood, Scott, 1986-; Duvigneau, Jordan; Craven, Matt (Vertical Entertainment, 2025)
An American woman spends more than ten years tracking down her daughter who was abducted and taken to the Middle East by the child's father.